Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Heads Together Terhadap Pemahaman Konsep Matematis Peserta DidikKelas IX SMPN 19 Padang - RAHNY BUSRA (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding of mathematical concepts is one of the purpose in mathematics learning which is expected to be mastered by every student. But in reality, understanding of mathematical concept of students in class IX of SMPN 19 Padang is still low. One effort can be made to improve understanding mathematical concepts of students by applying Numbered Heads Together of Cooperative Learning. This learning model helps students to develop their Understanding of mathematical concepts The type of research is a quasi-experimental design with Static Group Design. The final test result were analyzed by using the t-test. Based on the results of data analysis, it was concluded that understanding of mathematical concepts of students who learn with the cooperative learning model of Numbered Heads Together type are better than the understanding of mathematical concepts of students who learn by conventional learning. Keywords–Understanding of Mathematical Concepts, Numberes Heads Together, Conventional Learning